Wastes after distillation of Helichrysum italicum – biological active compounds and free radical scavenging activity - Nikolova, Milena; Dobreva, Ana; Berkov, Strahil (Acta Biologica Szegediensis, 2021)
Distillation wastewater, by-products from steam and water distillation as well as raw material used as control of ﬂower heads of Helichrysum italicum were comparative analyzed for content of the biologically active compounds by GC/MS. Acetone exudates, methanol extracts and ethyl acetate fractions obtained after alkaline hydrolyze of the studied materials were received. The three types of extraction products as well as the distillation wastewater were examined for free radical scavenging activity by DPPH assay. Phenol, fatty- and organic acids, sterols, triterpenes, sugars and sugar alcohols were identified. Succinic acid and myo-inositol were identified as main components of distillation wastewater. Hydroxycinnamic acid, caffeic acid and 4(p)-hydroxybenzoic acid were dominant compounds of the ethyl acetate fractions. Triterpenes and fatty acids, sterols and ﬂavonoids are among the main biologically active substances in the methanolic extracts and acetone exudates. The ethyl acetate fractions were found to possess the highest free radical scavenging activity (IC50 < 50 µg/mL). Significant differences in the activity between wastes and raw materials were not found. The results showed that the waste products after distillation of H. italicum contain important biologically active substances and the extracts with high antioxidant activity can be obtained from them.